The bacterial population adherent to plant particles in the rumen of reindeer fed lichen, timothy hay or silage - Monica Alterskjær Olsen; Svein Disch Mathiesen (Rangifer, 1998)
Male reindeer (Rangifer tarandus tarandus) calves taken from a natural winter pasture were given ad lib. access to lichen (n = 3), timothy silage (n = 3) and hay (n = 3) for 7 weeks. Median numbers of viable anaerobic bacteria adherent to the plant particles (cells/g wet weight of rumen solids), growing on a habitat simulating medium (M8V), were significantly higher (P = 0.05) in the rumen of reindeer fed lichen (26.5 x 109- 53.0 x 109) and hay (4.0 x 109- 40.5 x 109), compared to reindeer fed silage (1.15 x 109 - 3.25 x 109). Anaerobic bacterial strains (n = 551) from the plant particles obtained from the rumen of the nine reindeer examined, were isolated using an acid swollen cellulose medium (M8SC) and tested for their ability to hydrolyse carboxymethyl cellulose (CMC). The proportion of CMC hydrolysing adherent bacteria isolated from M8SC was significantly higher in reindeer fed hay (21.5%) compared ro animals fed lichen (5.3%) and silage (2.7%) (P = 0.05). The CMC hydrolysing bacterial srrains (n=42) isolated from reindeer fed hay where characterised as non-cellulolytic Butyrivibrio fibrisolvens (9.5%), cellulolytic B. fibrisolvens (50.0%), Clostridium sp. (2.4%) and unknowns (38.1%), while CMC hydrolysing strains (n=11) isolated from animals fed lichen and strains (n=4) isolated from animals fed silage where all characterised as B. fibrisolvens. None of the bacterial strains isolated from the rumen solids of reindeer fed lichen or silage were found to be cellulolytic. This study suggests that both lichen and timothy silage have a negative influence, compared to hay, on the numbers of cellulolytic bacteria adherent to the plant particles in the rumen of reindeer.